A Comprehensive Review of Comparative Interpretation of Holy Quran: Approaches, Methodologies, and Criteria for Establishing Plausible Interpretations - Ghulam Mustafa Nukhba (CV. AFDIFAL MAJU BERKAH, 2023)
The interpretation of the Quran has evolved over time, reflecting the exigencies, culture, and requirements of each era, as well as the diversity of methodologies and approaches adopted by scholars. Four main types of interpretation emerged: general interpretation, analytical interpretation, thematic interpretation, and finally, comparative interpretation. This study aims to review the concept and development of comparative interpretation, including its different approaches and methods, and the methodological criteria for determining the most plausible interpretation in this field. Additionally, the study seeks to clarify the principles and standards used in favoring and selecting the most robust and logical opinion.The study adopts a descriptive and analytical methodology, relying on reliable library sources. Several significant findings were obtained, indicating that the methodology of comparative interpretation involves identifying the subject and objectives, conducting meticulous comparisons between the opinions and approaches of interpreters, and discussing the relevant evidence based on specific methodologies. The study also emphasizes the importance of recording the comparison results and adopting the prevailing opinion based on credible evidence while avoiding reliance on uncertain views. Furthermore, the results indicate that comparative interpretation contributes to rectifying and adjusting the course of religious interpretation, eliminating weak opinions based on unsound foundations. Moreover, comparative interpretation provides opportunities to explore new perspectives and opens new horizons for ideas and minds, with the aim of developing a comprehensive approach that combines diverse interpretations.